2003
DOI: 10.1097/01.gme.0000055522.67459.89
|View full text |Cite
|
Sign up to set email alerts
|

A physiologic role for testosterone in limiting estrogenic stimulation of the breast

Abstract: These findings suggest that treatment with a balanced formulation including all ovarian hormones may prevent or reduce estrogenic cancer risk in the treatment of girls and women with ovarian failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 39 publications
(39 reference statements)
5
123
2
2
Order By: Relevance
“…Mechanistic evidence indicates that testosterone inhibits proliferation and stimulates apoptosis in breast epithelium (82,83). Analyses of observational data from the Women's Health Initiative study also showed that rates of estrogen receptor-negative breast cancer are inversely associated with circulating testosterone levels (80).…”
Section: Possible Effects Of Cross-sex Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic evidence indicates that testosterone inhibits proliferation and stimulates apoptosis in breast epithelium (82,83). Analyses of observational data from the Women's Health Initiative study also showed that rates of estrogen receptor-negative breast cancer are inversely associated with circulating testosterone levels (80).…”
Section: Possible Effects Of Cross-sex Hormonesmentioning
confidence: 99%
“…The role of testosterone in breast cancer is not clear. Some studies have suggested that testosterone may reduce proliferation and increase apoptosis by decreasing the expression of estrogen receptor in breast epithelium (82,83). On the other hand, an increased risk of breast cancer has been reported with increased serum testosterone levels in both pre-and postmenopausal women (89)(90)(91).…”
Section: Possible Effects Of Cross-sex Hormonesmentioning
confidence: 99%
“…Ar knockout transgenic models generally indicate that AR is required for normal mammary gland development (reviewed by Hickey et al (2012), Chang et al (2013) and Tarulli et al (2014)). In the human, AR appears to have a protective role in normal breast at least in part by opposing ERa action (Dimitrakakis et al 2003, Eigeliene et al 2012, Ochnik et al 2014. This raises the possibility of SARMs being used for breast cancer chemoprevention strategies in women with a high breast cancer risk.…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…In the breast tissue, testosterone is converted either to dihydrotestostone (DHT) by 5α-reductase or to 17β-estradiol (E2) by aromatase and can function as an AR or ERα agonist respectively, thus having a dichotomous effect on breast development (8,15). Studies have shown that testosterone is converted to E2 under estrogen deprivation, but is preferentially metabolized into DHT when both hormones are present at physiological levels, thus hampering the E2-induced effects (16,17). Maintenance of this balance ensures the physiological response of the mammary gland depending on the hormonal needs and the menopausal status.…”
Section: The Androgen-ar Axis In Normal and Cancerous Breast Tissuementioning
confidence: 99%
“…The high histological and molecular diversity of the heterogeneous diseases comprising ER -BrCa may partially explain the inconclusive results regarding the prognostic value of AR in this molecular subtype of the disease (49). In addition, in the absence of ER (ER-tumors), testosterone may preferentially be metabolized into DHT rather than E2, leading to more potent ARstimulation (8,16,17). On the other hand, AR has been associated with HER-2 overexpression in ER -tumors (63).…”
Section: Ar As a Potential Biomarker In Breast Tumorsmentioning
confidence: 99%